2018
DOI: 10.2991/j.jegh.2018.04.103
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Analysis of α- and β-Thalassemia and Sickle Cell Anemia in Southwest Iran

Abstract: This prospective study assessed the prevalence and genetic analysis of α - and β -thalassemia and sickle cell anemia (SCA) in Southwest Iran. Hematological indices were measured in 17,581 couples living in Khuzestan Province, Southwest Iran. Individuals with mean corpuscular volume <80, mean corpuscular hemoglobin <27, hemoglobin A2 ≥3/5 were considered as β -thalassemia traits. Prevalence of minor β -thalassemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…Based on the results of the present study, the prevalence of sickle cell hemoglobin in marriage applicants was 0.24 (24% for the total study years: 8% in 2014, 1% in 2015, 5% in 2016, 1% in 2017 and 9% in 2018). In the study by Foruzan Nejad et al in Ahvaz, the prevalence of sickle hemoglobin was 7.05% [14]. In the study by Canton et al and in the Kagura region, the respective prevalence was 10% [28].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Based on the results of the present study, the prevalence of sickle cell hemoglobin in marriage applicants was 0.24 (24% for the total study years: 8% in 2014, 1% in 2015, 5% in 2016, 1% in 2017 and 9% in 2018). In the study by Foruzan Nejad et al in Ahvaz, the prevalence of sickle hemoglobin was 7.05% [14]. In the study by Canton et al and in the Kagura region, the respective prevalence was 10% [28].…”
Section: Resultsmentioning
confidence: 91%
“…The results of the current study showed that the prevalence of alpha thalassemia in marriage applicants was 0.58 (58% in all study years: 1.4% in 2014, 1.5% in 2015, 1.4% in 2016, 1.4% in 2017, and 1.5% in 2018). In the study by Forouzan Nejad et al, the prevalence of α-thalassemia was 65.6% in Ahwaz [14]; in the study by Valizadeh et al, the prevalence of alpha thalassemia among marriage applicants was 53.3% [20]; in the study by Zandi et al, in Khuzestan, it was 9% [21], and in the southern regions of Iran, it was over 30% [22]. In the study by Alkara et al in Emirate, the respective prevalence was 49% [23], and in the study by Borgrus et al in Brazil, it was 42.8% [24].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The speci c phenotypes and frequency are shown in Table 6. The three most frequent types in Han people were -α 3.7 /αα, -α 4.2 /αα and -α WS , all of which were accompanied by CD41/42, accounting for 19.48%, 16.29% and 16.86% respectively. The three most frequent types in Li people were -α 3.7 /αα, -α 4.2 /αα and -SEA/αα, all of which were accompanied by CD41/42, accounting for 21.45%, 21.29% and 11.28%, respectively.…”
Section: Spectrum Of α-And β-Thalassemia Mutations Identi Ed In LI Anmentioning
confidence: 99%